Bionic gene delivery system activates tumor autophagy and immunosuppressive niche to sensitize anti-PD-1 treatment against STK11-mutated lung adenocarcinoma - Zhongquan Song; Qikai Wang; Hongjie Xiong; Jiang Xiao; Zihan Zhou; Tianxiang Li; Qian Sun; Liping Qiu; Yue Tan; Xiaohui Liu; Hui Jiang; Shuhua Han; et al. (Journal of Nanobiotechnology)
Abstract Clinical data have shown that Serine/Threonine Kinase 11 (STK11) mutation may be associated with an immunosuppressive tumor microenvironment (ITEM) and poor prognosis and failure of anti-PD-1 (αPD1) treatment in non-small cell lung cancer (NSCLC). To explore the potential of restoring STK11 protein in immunotherapy, a bionic gene delivery system was prepared by coating the STK11-encoded DNA-cationic polymer complex core with the tumor cell membrane, termed STK11@PPCM. STK11@PPCM could specifically bind with NSCLC cells and achieve precise delivery of STK11-encoded DNA. The released DNA effectively restored the STK11 protein expression, consequently reactivating autophagy and immunogenic cell death (ICD) in cancer cells. The liberated damage-associated molecular patterns (DAMPs) and autophagosome induced dendritic cells (DCs) maturation, which in turn enhanced CD8 + T cell infiltration, M1 macrophage polarization, and proinflammatory factor expression, thereby reversing the ITEM. Moreover, STK11@PPCM was also found to improve the sensitivity of cancer cells to αPD1 by increasing the expression of PD-L1, which was confirmed in STK11-mutated NSCLC cell xenografted mouse models, constructed by CRISPR-Cas9 knockout technology. This work demonstrated for the first time that restoration of functional STK11 can effectively reverse ITME and boost αPD1 efficacy in NSCLC, offering a new therapeutic approach for STK11-mutated lung adenocarcinoma in clinic. Graphical abstract